"I Spent a Full Month Bleeding, I Thought I Was Going to Die…" A Qualitative Study of Experiences of Women Using Modern Contraception in Wakiso District, Uganda. - Simon P S Kibira; Christine Muhumuza; Justine N Bukenya; Lynn M Atuyambe (PLoS ONE, 2015)
INTRODUCTION:There is high unmet need for family planning (FP) in Uganda as well as high contraceptive discontinuation rates. These contribute to the high fertility rates that in part are due to unplanned pregnancies. There are gaps in knowledge about experiences that couples go through while using contraceptives in their lives. This study explored women's experiences during the course of their contraceptive use. METHODS:We conducted a qualitative study involving 30 women who had used modern contraception for at least one year in Wakiso district, central Uganda. We used in-depth interviews to obtain their personal accounts. Index women were approached through health officers at four health centres in the district. All ethical approvals and informed consent were obtained. We used conventional content analysis; identifying codes through open coding, on which basis categories were developed and grouped into overarching themes. RESULTS:Women's accounts were summarised in the following themes: negative experiences with modern contraceptive use, motivation to continue using FP in spite of these negative experiences, the role of influential people, and discontinuation of use. Negative accounts dominated the experiences of most women but they expressed strong desire to continue using modern contraception even amidst all challenges. Health workers emerged as the most influential people that played a vital role in women's decisions. CONCLUSION:Varied negative experiences with modern contraception and misperceptions exist amidst a determination to continue use. Partner engagement, health service strengthening to improve side effects management and health worker skills, and engaging older women that have successfully used contraception as community champions, are potential strategies to support women's contraceptive decisions.